Fractography of clinical failures of indirect resin composite endocrown and overlay restorations - Saratti, Carlo M.; Rocca, Giovanni T.; Durual, Stéphane; Lohbauer, Ulrich; Ferracane, Jack L.; Scherrer, Susanne S. (Dental Materials, 2021)
Objectives: Compare failure modes and fracture origins using fractography on recovered clinically fractured parts of indirect resin composite endocrowns and overlay restorations on endodontically treated teeth (ETT). Methods: Four endocrowns (3 molars, 1 premolar) and one overlay (molar) adhesively luted on ETT were recovered after fracturing during function. The time in service ranged between 4 and 48 months. The composite materials were (i) CAD/CAM LAVA Ultimate (N = 1), (ii) Premise Indirect (N = 2), and (iii) Colombus (N = 2). Fractography was performed by means of digital microscopy and SEM. Occlusal surfaces were checked for signs of fatigue degradation and contact wear. Cuspal plane angles were measured from profiles obtained from 3D digital microscope images with respect to the horizontal plane of the occlusal central crown groove. Results: All five cases showed a wedge-opening mode I fracture, splitting the crown and tooth in two parts through the crown's central groove. Classic brittle fracture features (arrest lines, twist and wake hackle) were easily identified on the fracture surfaces. Multiple origins were located along the central groove in conjunction with the presence of fatigue cracks. Contact wear surfaces showed pitting and cracking. Cuspal plane angles were around 30–35°, except a 50° palatal cusp slope for the Lava Ultimate overlay. Significance: Fractography on clinical fractures of resin composites was enlightening. Occlusal surface fatigue degradation from cyclic loading, mode I fracture from applied mastication forces on cuspal planes, and stress concentration within the crown's central groove, indicate limitations of use of these materials for endocrowns in posterior teeth.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Clinical; Composite; Crown; Fatigue; Fractography; Fracture; Mode I; Restoration; Wear